Pengaruh Penggunaan Media Sosial Terhadap Prestasi Belajar Peserta Didik Pada Kelas XI MIPA di SMA Negeri 5 Padang - Nadya Pransisca Putri; Fifi Yasmi; Rici Kardo (Departement of Mathematics Education, 2023)
The background of this research is because there are students who use social media during the learning process. The purpose of this research is to describe; 1) the use of social media by Class XI MIPA students at SMA Negeri 5 Padang. 2) learning achievement of Class XI MIPA students at SMA Negeri 5 Padang. 3) Knowing the effect of using social media on the learning achievement of Class XI MIPA students at SMA Negeri 5 Padang.This research is a quantitative descriptive research with a simple linear regression analysis approach. The population of this study were all 252 class XI MIPA students at SMA Negeri 5 Padang. The sampling technique used purposive sampling technique as many as 72 people. The instruments used are questionnaires and documentation. Data analysis using percentage techniques and simple linear regression. The results of this study revealed that 1) the use of social media by class XI MIPA students at SMA Negeri 5 Padang was in the high category, 2) the learning achievement of class XI MIPA students at SMA Negeri 5 Padang was in the medium category, 3) the influence the use of social media on the learning achievement of class XI MIPA students at SMA Negeri 5 Padang, there is an effect of the use of social media by 7% with a very weak category on their learning achievement. It is recommended for teachers to make social media a place for students to be creative and a place for positive exchange of information, both lessons and things that have a good impact on students.